1977
DOI: 10.2337/diab.26.11.1052
|View full text |Cite
|
Sign up to set email alerts
|

Diminution of Bone Mass in Childhood Diabetes

Abstract: Photon absorption measurements of forearm bone density in 196 insulin-dependent patients, age 6--26 years, were compared with findings in 124 controls. Expected density, gm. Ca/cm.2 bone width (M/W), was calculated from regressions of M/W on ulnar length for white and black male and female controls. There were no significant correlations between M/W differences from expected and serum Ca, Mg, P, or alkaline phosphatase levels, estimated physical activity level, insulin dosage, or the presence of joint contract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(16 citation statements)
references
References 0 publications
2
11
1
2
Order By: Relevance
“…Previous BMD investigations in diabetic children at the forearm by peripheral quantitative computer tomography or single-photon absorptiometry showed a relative BMD decrease with estimates ranging from 5% to as much as 21% [1, 2, 3, 4, 5, 16]. It is not clear from our study why peripheral bone would be more significantly affected than the axial skeleton in diabetes disease.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Previous BMD investigations in diabetic children at the forearm by peripheral quantitative computer tomography or single-photon absorptiometry showed a relative BMD decrease with estimates ranging from 5% to as much as 21% [1, 2, 3, 4, 5, 16]. It is not clear from our study why peripheral bone would be more significantly affected than the axial skeleton in diabetes disease.…”
Section: Discussioncontrasting
confidence: 53%
“…The use of different techniques, measurements at different skeletal sites, inclusion of patients with different ages, duration of disease, degree of growth retardation and metabolic control might be responsible for these discordant findings. In the majority of these studies in diabetic children BMD was assessed at the level of the peripheral skeleton [1, 2, 3, 4, 5], whereas the experience with determinations at the level of the lumbar spine is limited [6, 7]. The lumbar spine contains mainly trabecular bone, which by its higher turnover rate compared to compact bone is more sensible to metabolic and endocrine changes, as observed in puberty, vitamin D deficiency and hypoparathyroidism [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial roles of insulin on skeletal health has been entertained by many authors [1], supported by the observations that lower BMD in type 1 diabetes [2,3] and higher BMD in subjects with type 2 diabetes [4,5]. We found that there are stronger associations of BMAD with fasting insulin and insulin AUC in AA adolescents.…”
Section: Discussionsupporting
confidence: 85%
“…[9] Many studies, though not all, carried out with the older techniques to measure BMD, like single photon absorptiometry (SPA) or dual photon absorptiometry (DPA), demonstrated that BMD is lower in adolescents and adults with T1DM compared to control population. [1011121314] Similar findings have been noted by the recent studies carried out using newer technologies to measure BMD like dual X-ray absorptiometry (DXA). [15161718] However, the data is not consistent among all the studies.…”
Section: Epidemiology Of Osteoporosis In Patients With T1dmsupporting
confidence: 67%